1979
DOI: 10.2527/jas1979.4961501x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Characteristics of Boars during and after Exposure to Increased Ambient Temperature2

Abstract: SummaryReproductive performance of 12 ll-monthold Yorkshire boars was determined during and after exposure to control or increased ambient temperatures. After 3 weeks adjustment at 23 C in temperature controlled chambers, six boars were heat stressed by exposure to 34.5 + 1.0 C for 8 hr and 31.0 • 1.0 C for 16 hr during each 24-hr period and six control boars were maintained at 23.0 + 1.0 C for 11 weeks. All boars were subsequently exposed to 23 C for 6 weeks. Semen was collected twice weekly before, during an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 10 publications
(22 reference statements)
1
10
0
3
Order By: Relevance
“…Boars when subjected to 32-34 C for three consecutive days have increased number of morphologically abnormal sperm cells and lowered sperm motility. Thus, elevated temperature conditions are detrimental to spermatogenesis (Wettemann et al, 1979). Similar observations were reported by Tummuruk et al(2002) in Thailand on the seasonal effects of high ambient temperature on reproductive performance of sows.…”
Section: Heat Stresssupporting
confidence: 82%
“…Boars when subjected to 32-34 C for three consecutive days have increased number of morphologically abnormal sperm cells and lowered sperm motility. Thus, elevated temperature conditions are detrimental to spermatogenesis (Wettemann et al, 1979). Similar observations were reported by Tummuruk et al(2002) in Thailand on the seasonal effects of high ambient temperature on reproductive performance of sows.…”
Section: Heat Stresssupporting
confidence: 82%
“…Previous experimental data from animal models suggested that scrotal heat stress may be a reversible method for contraception [35]. In boars, the number of spermatozoa was not affected in many heat experiments, but motility and the percentage of normal spermatozoa fell between 1 and 6 weeks after the heat exposure; when the heating was for only a limited period, motility and the percentage of normal spermatozoa recovered after about 6 weeks [36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…2 Elevated ambient temperatures have similar detrimental effects on the boar, resulting in decreases in both the motility and quantity of sperm and increases in the proportion of abnormal sperm. 4 Some studies have demonstrated that elevated temperatures significantly decrease ovulation rate, 2,5 while another study revealed no such effect. 6 Edwards et al 5…”
Section: Designmentioning
confidence: 99%